Assessing the 2019 rubella elimination status in the Russian Federation - T. S. Chekhlyaeva; O. V. Tsvirkun; N. V. Turaeva; D. V. Erokhov; L. A. Barkinkhoeva; N. T. Tikhonova (Инфекция и иммунитет, 2021)
In 2002, the WHO Regional Office for Europe developed the Strategic Program for the Prevention of Measles and Congenital Rubella Infections in the European Region, which was revised in 2004. As a result of the revision, an additional target was set to eliminate endemic rubella in the region by 2010. Rubella is a disease well controlled by vaccination that accounts for a theoretical potential to interrupt its global transmission. Since 2013, the Russian Federation has been implementing the National Rubella Elimination Program. Elimination criteria have been revised as the Program proceeds. Currently, the main criterion for rubella elimination is the absence of endemic (local) virus transmission for at least 36 months, which should be confirmed by molecular genetic research methods. In addition, in the Russian Federation, an incidence rate of less than 1 case per 1 million population is also used as one of the elimination criteria. Since 2013, due to a high (over 95%) coverage of preventive vaccinations a decrease in incidence rates and their stabilization at a level of less than 1 per 1 million population since 2014 state in favor of successfully implemented Program. Genetic monitoring of rubella virus strains circulating in human population noted the termination of endemic virus transmission. While implementing the Elimination Program, the prevailing virus genotypes that circulate in Russia were found to be genotypes 1E and 2B showing a global distribution. The data obtained after molecular genetic monitoring allowed to find that the strains isolated during this period belonged to different clusters accounting for in favor of being imported. Considering the above factors such as high vaccination coverage, low incidence rate and lack of endemic virus transmission, the 2017 WHO Committee on verification of measles and rubella elimination assigned the Russian Federation the status of a country that has achieved rubella elimination. The continuation of the phase of infection elimination is confirmed annually. This article presents the results on comprehensive assessment of rubella elimination status in the Russian Federation by specialists from the National Scientific and Methodological Center for Measles and Rubella and WHO EURO Moscow regional reference laboratory for measles and rubella based on 2019 epidemiological data and molecular genetic studies.